Urban and rural mortality and survival in Medieval England - Brittany S. Walter; Sharon N. DeWitte (Taylor & Francis Group, 2017)
Background: Late medieval England underwent intensive urbanisation, particularly in its largest city: London. Urban dwellers were exposed to factors such as high population density, elevated risk of infection, unsanitary living conditions and precarious food supplies. Aim: To assess whether the urban environment was more detrimental to health than the rural environment, this study compares risks of mortality and survival, as proxies for health, in medieval urban vs rural England. Subjects and methods: This study uses samples from rural St. Peter's cemetery in Barton-upon-Humber, Lincolnshire (c. 1150-1500) and urban St. Mary Spital cemetery in London (c. 1120-1539). Cox proportional hazards analysis and Kaplan-Meier survival analysis are used to assess differences in mortality and survival between urban and rural environments, including differences between sexes. Results: The results indicate that urban adults faced elevated risks of dying and reductions in survivorship. Specifically, urban females faced elevated risks of dying and reductions in survivorship, while the risks for males were similar in both environments. Discussion: These results suggest that the effects of urbanisation in medieval England varied by sex. Deleterious conditions associated with urbanisation in London were hazardous for adults, particularly females who may have migrated into London from rural areas for labour opportunities.